080 A quality improvement project on the management of convulsive status epilepticus at ICHT. Issue 12 (14th November 2019) - Wade, Charles; Evans, Matthew; Osugo, Martin; Quinn, Taryn; Dorsey, Rachel; Everett, Alex; O'Dwyer, John; Johnson, Mike; Gorgoraptis, Nikos
Abstract : Convulsive status epilepticus (CSE) is a common neurological emergency with significant morbidity and mortality. We developed a CSE management protocol for a tertiary neurosciences centre with the aim of standardizing practice and increasing the likelihood of favourable outcome. To do this we undertook a questionnaire-based audit of current management principles in A&E staff (n=24), as well as a retrospective case-based audit of 3-months of acute seizure presentations in the same department (n=-103). We identified variable understanding of optimal management, lack of awareness/availability of informative resources and subsequent suboptimal management. Following this we developed and implemented a trust-wide CSE management protocol based on national guidance, literature review and the local expert opinion of neurology consultants and neuroscience pharmacists. The protocol covers early, established and refractory CSE and includes pharmaceutical management, important investigations/observations and who to involve and when. The protocol was published on the trust Intranet and summary flowchart posters were displayed in A&E. We organised teaching sessions for A&E staff and those involved in acute medicine. Though not complete at time of abstract submission, we intend to re-audit CSE management in the near future, assessing protocol adherence and will also present the results of this.